The Existance of National Sharia Arbitration Agency in The Settlement of Sharia-law Banking Dispute In Rejang Lebong District - Harianto Wijaya; Laras Shesa (Institut Agama Islam Negeri (IAIN) Curup, 2021)
Purpose: The purpose of the study was to figure out how the existence of the national sharia arbitration body was in the settlement of sharia banking disputes in Rejang Lebong district. With the writhing of sharia-based economies, it certainly does not seal the possibility of a problem arising from it. In terms of matters resolved without need to to the realm of the court whether it has gone through a national sharia arbitration body or not yet.Design/Method/Approach: In the drafting of this article the author uses a qualitative approach. To search for data in this study constituents used interview methods with specific respondents. Analyzed it with deductive techniques. So that it could be narrated the results of those findings.Findings: The findings in this study turned out that the existence of national sharia arbitration agencies was still minimal, this being because of some of the first minimal financial or business institutions that used sharia foundations as a foundation in transacting. Second, still the lack of community understanding of the existence of national sharia arbitration institutions. For the problem settled ligitally only, many did not yet know it should be settled in the Court of Religion. Many societies who assume such things will be settled in ordinary public courts. Third, based on the recognition of bank leaders using the principle of sharia transactions, there was indeed no dispute at the bank yet.Originality/Values: The conclusion that can be drawn from research findings is the absence of existence from national arbitration agencies within the economic problems of the community of Rejang Lebong County